A comprehensive review of the role of the hedgehog pathway and vismodegib in the management of basal cell carcinoma. (17th March 2015) - Erdem, Gökmen Umut; Sendur, Mehmet Ali Nahit; Ozdemir, Nuriye Yıldırım; Yazıcı, Ozan; Zengin, Nurullah
Abstract: Background: Basal cell carcinoma (BCC) is the most common cancer. Most cases of BCCs are treated with only optimal surgical resection. However, unresectable, locally advanced or metastatic tumors might have potential to progress. In this patient group, there is no standardized treatment approach. Vismodegib is a new selective inhibitor of the hedgehog (Hh) pathway. This manuscript is aimed to review the efficacy of the Hh pathway inhibitor vismodegib in BCC patients with locally advanced or metastatic disease. Scope: Vismodegib showed positive results in clinical studies. A computerized search of the PubMed and American Society of Clinical Oncology Meeting abstracts was performed, by searching for the following keywords: 'vismodegib', 'pathway', 'inhibitor', and 'targeted therapies for BCC'. The last search was done on 1 September 2014. Most of the vismodegib data depend on phase I and II trials. Findings: Preclinical and clinical studies have shown that Hh pathway activation occurs in BCC. In BCC patients the role of chemotherapy is not completely known. Although conventional chemotherapies like cisplatins increase the response rate in BCC, improvement in overall survival and progression free survival were not demonstrated. Results of both phase I and phase II studies have shown that vismodegib is a potential new treatment strategy for patients with locally advanced and metastatic BCC. As in previously published phase I trials, in the ERIVANCE BCC study the primary endpoint, objective response rate, significantly increased by 43% and 30% in patients with locally advanced and metastatic BCC, respectively. Because of the promising results in phase I and II trials, vismodegib was approved by the Food and Drug Administration (FDA) in the treatment of patients with BCC who are not suitable for surgery or radiotherapy or with relapsed locally advanced disease following surgery or metastatic disease. Conclusion: Recent trials have shown that vismodegib has produced promising activity in patients with locally advanced and metastatic BCC. The ongoing studies with vismodegib in other solid tumors and BCC will shed light on more certain treatment pathways.